PENGARUH HARGA, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN (Studi kasus konsumen Grab di Kelurahan Pakis Jajar Kab Malang) - Muhammad Hawin Khulugi; M Hufron; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted to determine the effect of price, promotion and service quality on Grab service purchase decisions. This research was conducted in the village of Pakis jajar Malang Regency. This type of research uses quantitative data, i.e. the data can be obtained through, observation or downward direct spaciousness, and data sources used are primary data and secondary data. The sample calculation in this study uses the Slovin formula which produces 93 respondents. The results of this study are the price, promotion and service quality variables have a positive and significant influence on purchasing decisionskeywords: Price, promotion of service quality and purchasing decisions